Criterion Analysis and Content Validity for Standardized Behavioral Tests in a Detector‐Dog Breeding Program1. (20th November 2014) - Rocznik, Dorothee; Sinn, David L.; Thomas, Scott; Gosling, Samuel D.
Abstract: Many working‐dog programs assess behavior during a dog's first year of life with the aim of predicting success in the field. However, decisions about which tests to administer are frequently made on the basis of tradition or intuition. This study reports results from a survey given to U.S.A.'s Transportation Security Administration (TSA) detection‐dog handlers (N = 34). We categorized and summarized handlers' responses regarding traits they felt were important for work. We used this criterion analysis to examine the content validity of the TSA's puppy tests. Results indicate that 13 of 15 traits that are currently being measured are relevant. However, several traits not currently measured were identified as being highly important, notably "play" and off‐duty "calmness." These results provide support that the TSA tests are measuring traits relevant to operational search team performance but also highlight other traits that may be profitable to assess in this and other detection‐dog programs.